HUMANITARIAN TURN IN CONTEMPORARY ISLAMIC STUDIES: A REFLECTION OF ALI ZAIN AL-JUFRI’S THOUGHT ON RELIGIOUS MODERATION - Imad Syauqi; Wawan (Al'Adalah, 2023)
This research aims to examine Ali Zain al-Jufri's religious moderation. Through his work, al-Insaniyya qabla al-Tadayyun (Humanity before Religiosity), al-Jufri responds to the religious forms of Muslims in several parts of the world. By focusing on this work, the researchers thoroughly explore al-Jufri's thoughts regarding religious moderation. Why is this work relevant for study? Apart from the fact that no previous research has examined al-Jufri's work, this work is increasingly relevant to study if we reflect on current sociological facts. Much violence occurs in the name of religion. Those behaviors are nothing more than forms of interpretation, which are then considered the voice of God. At least, al-Jufri's work is one way out as an oasis to these problems. The method used in this research is a review-based qualitative method that focuses on examining al-Jufri's work. This research is classified as library research. In the end, this research concluded that there are three significant values of al-Jufri's religious moderation, including the command to speak good words (Surah al-Baqarah [2]: 83), the prohibition on killing fellow humans (Surah al-Ma'idah [3]: 32), and the order to uphold justice on earth (Surah al-Nisa [5]: 135). Therefore, al-Jufri distinguished religion and religiosity. Humanity, for him, is above religiosity, not religion.